1998
DOI: 10.1002/etc.5620170406
|View full text |Cite
|
Sign up to set email alerts
|

Trophic transfer of silver to marine herbivores: A review of recent studies

Abstract: Abstract-We review recent progress in understanding the trophic transfer of silver (Ag) in marine herbivores, especially mussels that have been extensively used as biomonitors of coastal contamination. A bioenergetic-based kinetic model is invaluable in predicting the trophic transfer and bioaccumulation of Ag in aquatic animals. Critical parameters that need to be quantified in predicting trophic transfer include Ag assimilation efficiency (AE) from ingested food particles, animal feeding rates, and Ag efflux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Thus, it would be expected that simultaneous silver accumulation from both dissolved phase and food would increase the whole body silver accumulation and consequently the acute silver toxicity in the copepod A. tonsa. In fact, it was shown that the silver accumulated by copepods correspond to that present in the cytosolic fraction of phytoplankton food [31,36]. Furthermore, no changes were observed in higher salinities (Figs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, it would be expected that simultaneous silver accumulation from both dissolved phase and food would increase the whole body silver accumulation and consequently the acute silver toxicity in the copepod A. tonsa. In fact, it was shown that the silver accumulated by copepods correspond to that present in the cytosolic fraction of phytoplankton food [31,36]. Furthermore, no changes were observed in higher salinities (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…Both T. weissflogii and T. pseudonana have already been employed in recent studies on metal transfer in marine herbivores [15,[31][32][33][34]. Both T. weissflogii and T. pseudonana have already been employed in recent studies on metal transfer in marine herbivores [15,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ag may accumulate as an insoluble sulphide complex, which is very stable, in Percentage of Ag (%) retained by green mussels following 6 d of feeding on radiolabelled food in different seasons (mean ± SD, n = 12). The efflux rate constant (k e ) was calculated from the slope of the regression between the natural log of the percentage of Ag retained from 7 d and the time mussels (Fisher & Wang 1998). The estuarine population had relatively more Ag in the MTLP (2-to 4-fold); thus, MTLP may also share some detoxification roles.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic invertebrates are exposed to chemicals from both the particulate and dissolved phases. Recently, there have been renewed interest and new revelations in the trophic transfer of contaminants in aquatic food chains as food uptake has been increasingly recognized as an important source for contaminant accumulation [1–6]. One critical parameter in understanding and modeling a contaminant's trophic transfer and accumulation in aquatic systems is the assimilation efficiency (AE) of the contaminant in animals from ingested food [7, 8].…”
Section: Introductionmentioning
confidence: 99%